Internasionalisasi Pembelajaran Pemasaran Digital: Implementasi Service Learning Berbasis Studi Kasus UMKM Indonesia Di UITM Kuala Lumpur - Satria Tirtayasa; Ahmad Afandi (Athallah Publishing Globalndo, 2026)
Amidst the increasingly integrated ASEAN economic landscape, the ability of Micro, Small, and Medium Enterprises (MSMEs) to adopt digital marketing has become an imperative, yet higher education institutions often face limitations in providing cross-national comparative insights. This knowledge gap, particularly for the academic community at Universiti Teknologi MARA (UiTM) Kuala Lumpur, whose materials focus on the domestic Malaysian context, hinders the development of a regionally relevant curriculum. Responding to this issue, this community service activity was designed to bridge this gap with the aim of enhancing the digital marketing literacy and practical skills of 40 UiTM lecturers and students. The program utilizes the Indonesian MSME ecosystem as a case study laboratory to provide a deep understanding of strategic concepts like Segmentation, Targeting, Positioning (STP) and the customer journey, train participants in campaign plan development, strengthen Indonesia-Malaysia comparative insights, and initiate an academic collaboration network. This activity was implemented using a Service Learning (SL) approach in the format of a full-day interactive workshop at the UiTM Kuala Lumpur Campus. The learning process was systematically designed, combining a knowledge-sharing session on the Indonesian MSME landscape with in-depth material structured into four modules: foundations of digital marketing strategy (STP, marketing funnel); selection and optimization of marketing channels (social media, marketplace); creative content development strategy (copywriting, storytelling); and an introduction to digital advertising and Key Performance Indicator (KPI)-based performance measurement. The culmination of this method was a guided practical session where participants worked in groups to apply all concepts to develop a comprehensive digital marketing campaign plan based on a provided Indonesian MSME case study. The program evaluation revealed highly positive outcomes. From a cognitive aspect, there was a significant increase in participant understanding, with a comparative analysis of pre-test and post-test scores showing an average knowledge improvement of 45%. From a psychomotor aspect, success was reflected in the concrete outputs of structured and applicable draft digital marketing plans from each group, encompassing audience analysis, channel selection, content pillar ideas, and realistic KPI setting. A prominent qualitative result was the strengthening of comparative insights, which emerged during the final discussion session where participants actively compared the digital ecosystems of Indonesia and Malaysia. This success was also marked by the opening of a dialogue for further collaboration between the two institutions. It is concluded that this community service activity was holistically successful, not only in transferring technical knowledge and practical skills but also in building an essential cross-cultural bridge of understanding in the ASEAN economic era. This program effectively proved that the use of cross-national case studies can be a powerful learning tool to enrich teaching materials and prepare a more regionally competitive human resource. The primary significance of this activity lies in its affirmation that the cross-national Service Learning model is an innovative approach capable of producing a dual impact: enhancing individual capacity and strengthening sustainable institutional relationships.